2007
DOI: 10.1002/art.22298
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cartilage growth: Modulation of balance between proteoglycan and collagen in vitro using chondroitinase ABC

Abstract: Objective. To examine the cartilage growthassociated effects of a disruption in the balance between the swelling pressure of glycosaminoglycans (GAGs) and the restraining function of the collagen network, by diminishing GAG content prior to culture using enzymatic treatment with chondroitinase ABC.Methods. Immature bovine articular cartilage explants from the superficial and middle layers were analyzed immediately or after incubation in serumsupplemented medium for 13 days. Other explants were treated with cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
91
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 42 publications
14
91
0
Order By: Relevance
“…The bulk of the immature cartilage is often described as having a fairly isotropic structure with chondrocytes arranged at random (25,26). However, cell density may decrease with depth, particularly near the articular surface (25), whereas GAG and collagen concentrations and tensile and compressive moduli may increase (27,28). On the other hand, mature articular cartilage possesses distinct superficial, middle, and deep zones.…”
Section: Growth and Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…The bulk of the immature cartilage is often described as having a fairly isotropic structure with chondrocytes arranged at random (25,26). However, cell density may decrease with depth, particularly near the articular surface (25), whereas GAG and collagen concentrations and tensile and compressive moduli may increase (27,28). On the other hand, mature articular cartilage possesses distinct superficial, middle, and deep zones.…”
Section: Growth and Maturationmentioning
confidence: 99%
“…3). It has been hypothesized that changes in cartilage size and in maturation (as quantified by the tensile properties) could result by altering the balance of proteoglycan and collagen metabolism (27,41,42). Culturing immature cartilage explants with fetal bovine serum (FBS), insulin-like growth factors-1, or bone morphogenetic protein-7 (BMP-7) resulted in an expansive growth phenotype characterized by large increases in size, stimulation of proteoglycan in excess of collagen, and decreases in tensile stiffness and strength (42).…”
Section: Growth and Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect, but dramatic contribution of the proteoglycan component to the tensile properties or cartilage has also been demonstrated. Chondroitinase ABC (C-ABC) treatment, which specifically depolymerizes chondroitin and dermatan sulfate GAG chains [10], resulted in a reduction of the initial slope of the stress-strain curve [11,12] and an increase in the overall tensile modulus of cartilage [13][14][15] and tensile strength in tendon [16]. In addition, collagen to proteoglycan ratio correlated strongly with equilibrium tensile modulus of cartilage [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous experimental studies showed significant influences of the synthesis rate of PGs and collagen on mechanical properties of the cartilage explants (Asanbaeva et al 2007) and TE constructs (Bian et al 2009). Effects of such phenomena on post-implantation mechanical performance of TE implants have not been reported so far, and it is unknown how different synthesis rate of the PGs and collagen during TE process may change mechanical conditions in TE implants after implantation.…”
Section: Introductionmentioning
confidence: 98%